Interdisciplinary perspectives on international law and international relations : the state of the art - Dunoff, Jeffrey L. , 1960-; Pollack, Mark A. , 1966- (Cambridge : Cambridge University Press, 2013)
"International Law and International Relations: Insights from Interdisciplinary Scholarship brings together the most influential contemporary writers in the fields of international law and international relations to survey what we know about the making, interpretation, and enforcement of international law. The contributions to this volume critically explore what recent interdisciplinary work reveals about the design and workings of international institutions, the various roles played by international and domestic courts, and the factors that enhance compliance with international law. The volume also explores how interdisciplinary work has advanced theoretical understandings of international law"-- Provided by publisher
"This book brings together the most influential contemporary writers in the fields of international law and international relations to take stock of what we know about the making, interpretation and enforcement of international law"-- Provided by publisher
Includes bibliographical references and index
Keywords: Effectiveness and validity of law; International law; International relations